Sobre el anillado de aves en la Argentina: recuperaciones y recapturas - Rumboll, Mauricio; Capllonch, Patricia; Lobo, Rebeca; Punta, Gabriel (Nuestras Aves, 2005)
Este artículo no cuenta con un resumen.